The Concept of the Restoration Project of the Hryhorii Skovoroda Museum in the Context of Preserving Ukrainian Cultural Heritage Objects - Viktor Severyn; Nadiia Severyn (Культура і мистецтво у сучасному світі, 2024)
The aim of the article is to present the concept of the project decision regarding the restoration of the Hryhorii Skovoroda Museum taking into account the preservation of objects of Ukrainian cultural heritage. Results. The foreign and domestic experience of preserving cultural heritage in the context of the world culture, which forms the basis of the elaborated project, is analysed. The development strategy and the main reconstruction goals of the Hryhorii Skovoroda Museum are determined. In the architectural and planning decision, it is aimed to use such compositional techniques as symmetry and geometry. It is mentioned that the forming elements of design are created on the basis of images associated with the life of H. S. Skovoroda or heroes of his creative works. Measures for restorating garden and park ensemble and the restoration project of H. S. Skovoroda’s museum as an object of cultural heritage of national significance are offered. Scientific novelty. The concept of the mentioned project offers directions for restorating the Hryhorii Skovoroda Museum that meet modern requirements for creating museum exhibits with mandatory consideration of universal design (inclusive design), aimed at meeting such requirements as accessibility, safety, informativeness, convenience, environment comfort for all people, particularly with various health disabilities (physical, psychological, etc.), and of different age category. Conclusions. The museum’s development strategy involves spreading knowledge about Hryhorii Skovoroda, attracting a wide range of the museum visitors, ensuring the full functioning of the museum as a scientific, cultural and educational institution, its further development as a centre of cultural and artistic life. Involvement of architectors and environment designers can allow to create a project offer for the new building and museum interiors, taking into account the preserved exhibition objects. Functionality and ergonomics of this museum areas are planned in such a way that people with disabilities can have an opportunity to visit the exhibition without any obstacles. An important element in the development of interior design is lighting and usage of elements with the modern technologies. Therefore, the creation of a museum exposition is a complex task, which can be realised due to the synthesis of the designer’s creative ideas, the system of images, objects, events, phenomena and innovative interactive technologies, which create a complete picture, such as an exhibition image.